2016
DOI: 10.1177/0956797616654677
|View full text |Cite
|
Sign up to set email alerts
|

Strategically Stunning

Abstract: The phenomenon of increased desire for, and use of, appearance-enhancing items during times of economic recession has been termed the lipstick effect The motivation underlying this effect has been attributed to women's desires to enhance their attractiveness to financially stable partners (Hill, Rodeheffer, Griskevicius, Durante, & White, 2012). In the present research, we found evidence for our proposal that during times of economic recession, the heightened economic concern experienced by women translates in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(15 citation statements)
references
References 34 publications
1
11
0
1
Order By: Relevance
“…Consistent with previous research (Dhir et al, 2016;Elias & Gill, 2017;Varghese, 2017), we found that women are more likely to use skin-lightening filters than men when posting on social media. This is consistent with research suggesting that women attend more to their appearance than men (Bhogal et al, 2016;Uss et al, 2020;Krems et al, 2020;Kulesza et al, 2014;Netchaeva & Rees, 2016;Parrett, 2015).…”
Section: Filters Sex and Skin Tonesupporting
confidence: 90%
See 1 more Smart Citation
“…Consistent with previous research (Dhir et al, 2016;Elias & Gill, 2017;Varghese, 2017), we found that women are more likely to use skin-lightening filters than men when posting on social media. This is consistent with research suggesting that women attend more to their appearance than men (Bhogal et al, 2016;Uss et al, 2020;Krems et al, 2020;Kulesza et al, 2014;Netchaeva & Rees, 2016;Parrett, 2015).…”
Section: Filters Sex and Skin Tonesupporting
confidence: 90%
“…Compared to men, women tend to be more concerned with, judged more for, and experience more consequences based their appearance (Buss et al, 2020). As a result, women are more likely to alter their appearance for socially utilitarian reasons (Krems et al, 2020), such as more attractive women being more likely to receive help from strangers (Bhogal et al, 2016), attractive servers earning more tips from customers (Parrett, 2015), women wearing cosmetics sell more retail products (Kulesza et al, 2014), and women concerned with economic scarcity are more likely to alter their appearance for the acquisition of resources (Netchaeva & Rees, 2016).…”
Section: Filtersmentioning
confidence: 99%
“…For example, economic uncertainty is associated with higher purchases of beauty products by women (Hill, Martin, et al, 2012;Hill, Rodeheffer, et al, 2012). Women may purchase more beauty products in order to secure greater resource stability, which likely bolsters their sense of control (Hill, Martin, et al, 2012;Hill, Rodeheffer, et al, 2012;Netchaeva & Rees, 2016).…”
Section: The Environmental Uncertainty Perspectivementioning
confidence: 99%
“…However, these cues consistently increased women's desire for products that increase attractiveness to mates" (p. 1). Subsequent research by Netchaeva and Rees (2016) extended these findings by showing that "during times of economic recession, the heightened economic concern experienced by women translates into increased desire to use appearance-enhancing items to both attract romantic partners and create a favorable impression of themselves in the workplace, as both strategies can help women become secure financially" (p. 1). Both papers are consistent with the overall notion that individuals are strongly attuned to the state of the economy, with profound influences for basic psychological functioning, spanning from how people understand causality to how they think about beauty, mating, and survival.…”
Section: Of 10mentioning
confidence: 99%